Runoff trend and potentiality in Melaka Tengah catchment of Malaysia using SCS-CN and statistical technique. Issue 4 (1st October 2016) - Shirazi, Sharif Moniruzzaman; Adham, Ibrahim; Othman, Faridah; Zardari, Noorul Hasan; Ismail, Zubaidah
Abstract: This study is focused to identify the surface runoff trends and potentiality of the five watersheds transforming the discrete runoff pattern to smooth patterns. Runoff potentiality was analyzed by Soil Conservation Service Curve Number (SCS-CN) technique. Considering Hydrologic Soil Group (HSG) and percentage of particular land use pattern, weighted CNs of five watersheds were found between 82 and 85. Monthly surface runoff trends were investigated by statistical autocorrelation, Mann-Kendall, Sen slope and lowess methods. According to the Mann-Kendall method, no statistical significant monotonic trends were found for all the watersheds. Smoothing curve analysis reveals that the monthly mean runoff is 30 mm, 34 mm, 39 mm, 28 mm and 37 mm and the percentage of runoff is 23%, 25%, 31%, 25% and 26% for the watersheds 1, 2, 3, 4 and 5, respectively. Degree of effect of several land use pattern with corresponding soil type was analyzed to assess the total runoff volume for contributing to the surface water resources. Result shows that 26% of the rainwater contributes to the surface runoff of Melaka Tengah catchment and provides the information for planning of surface water management and potentiality of groundwater recharge.